Spectrophotometric Evaluation of Anterior Maxillary Tooth Color Distribution According to Age and Gender - Karaman, Tahir; Altintas, Eyyup; Eser, Bekir; Yildirim, Tuba Talo; Oztekin, Faruk; Bozoglan, Alihan (Wiley, 2019)
Purpose To determine the effects of age and gender on the color distribution of the right maxillary central, lateral incisors, and canine teeth. Materials and Methods The tooth color was measured using the VITA Easyshade V spectrophotometer with a total of 202 volunteers (89 men, 113 women). The age distribution in this study was between 15 and 70 years old (average: 31). A grey background color was used to prevent background reflection while performing the color measurements. Results According to the VITAPAN Classical shade guide, the tooth color distribution of the central and lateral incisors showed a maximum of A2, with a maximum of B3 for the canine teeth. When comparing the International Commission on Illumination L-*, a(*), and b(*) values (CIELab color space coordinates) of the teeth with subject gender, statistically significant differences were not found between gender and the L-* and b(*) values (p > 0.05); however, a statistically significant difference was observed between gender and the a(*) values (p < 0.05). Conclusion When the distribution ratio of tooth color was examined, different ratios were determined based on gender and age and between the maxillary central, lateral incisors, and canine teeth. A uniform tooth color should not be chosen for anterior restorations, and factors such as gender and age should be considered when making a color selection for patients.
Keywords: Color analysis; spectrophotometry; tooth color measurement